Phytochemical Screening, in vitro Antioxidant and Anti-inflammatory activity of Freeze-dried Borassus flabellifer L. Seed Powder - Banu, Saira Mariam; Vigasini, Nora; Surenderan, Shanmugapriya (Asian Journal of Biological and Life Sciences)
Palmyra palm tree, native to Tamil Nadu bears seasonal summer fruits (Nungu) with numerous health benefits. Preserving the fruit throughout the year is essential to enjoy its goodness and health benefits. With this focus, the aim of the present study was to evaluate the phytochemical profile, in vitro antioxidant and anti-inflammatory activity of Borassus flabellifer seed and seed coat in the freeze-dried form. Aqueous seed powder extract was used in this study. Phytochemicals were quantified using standard methods. Bioactive compounds were identified using GC-MS. Radical scavenging potential was evaluated using DPPH, Hydrogen peroxide and Nitric oxide radical scavenging assays. Anti-inflammatory potential was evaluated using Albumin denaturation assay. Statistical significance of mean values was tested using One-way ANOVA followed by Tukey’s test and IC50 value was calculated by non-linear regression analysis using GraphPad. Saponins, tannins, terpenoids, steroids, glycosides, flavonoids, alkaloids and phenols were present in the sample. The aqueous seed powder extract exhibited potent radical scavenging activity in a dose dependent manner and the IC50 value of DPPH, Hydrogen peroxide and Nitric oxide radical scavenging assay was 415.91, 1080.19 and 13.489 μg/mL respectively. The aqueous extract also exhibited potent protein denaturation inhibitory activity with an IC50 value of 1174.9 μg/mL. Results indicate that the phytochemical compounds present in the seed powder could have largely contributed to its good antioxidant and anti-inflammatory activity.
Keywords: Anti-inflammatory; Antioxidant; Borassus flabellifer; Freeze-dried; Phytochemicals